An Amuletic Papyrus from Theban Tomb 233 and the FourAkh-spirits - Ockinga, Boyo G. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2020)
Publication of an amuletic papyrus of the early post-Ramesside Period found in the tomb of Saroy (TT233) invoking the protection of the four akh-spirits. The text, which is the earliest attested to specify the names of the spirits, is analysed in the context of the known parallel texts and of the references to the four spirits.